INFLUENCE OF TOPOGRAPHY OF THE SURFACE OF DETONATING COATINGS MADE OF TiAl3+ГА (Ca10(PO4)6(OH)2) COMPOSITES ON BIOLOGICAL COMPATIBILITY - Sitnikov, A. A.; Yakovlev, V. I.; Zhakupova, A. E.; Popova, A. A.; Demisinova, S. S.; Sharkeev, Yu. P.; Legostaeva, E. V.; Terehin, S. B. (Recent Contributions to Physics, 2017)
In the paper results on research calcium-phosphatic of coverings on the titanic basis, applied in implants for replacement at loss or destruction of a bone live organism are resulted